INCREASING THE KNOWLEDGE OF BUMDES MANAGERS IN ACCORDANCE WITH GOVERNMENT REGULATIONS IN KEPAHIANG DISTRICT, KEPAHIANG REGENCY, BENGKULU PROVINCE - Baihaqi, Baihaqi; Hatta, Madani; Carolina, Ovita; Hasnin, Hannisa Rahmaniar; Pujawati, Pujawati (LPPM Univ. Ibn Khaldun Bogor, 2025)
In general, Village-Owned Enterprises (BUMDes) in the Kepahiang District are not operating effectively. This is due to inactive management, non-operational BUMDes, and limited capacity to develop business initiatives. As a result, BUMDes have not generated income, and capital from villages remains idle in banks. However, the region holds significant potential, such as home-based food industries (e.g., opak, rengginang, tape uli, teng-teng), tourist attractions, waste processing, and event facility rentals. This community service activity aimed to empower and enhance the village economy by providing knowledge on BUMDes management, exploring business potential based on village characteristics, and emphasizing the importance of collaboration. The event was held in October 2024 for six hours at the Bogor Baru Village Hall, using presentations and discussions as methods. It was attended by 42 participants, including village officials, BUMDes managers, and local residents. The material covered BUMDes establishment, business potential identification, resource analysis, and examples of successful BUMDes. Discussions were interactive, allowing participants to ask questions and engage actively. Participants expressed hope for the continuation of such programs to strengthen BUMDes management capacity and raise public awareness about the economic benefits of BUMDes.